2019
DOI: 10.3390/ijms20133170
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Prediction of PAMPA Effective Permeability Using a Two-QSAR Approach

Abstract: Oral administration is the preferred and predominant route of choice for medication. As such, drug absorption is one of critical drug metabolism and pharmacokinetics (DM/PK) parameters that should be taken into consideration in the process of drug discovery and development. The cell-free in vitro parallel artificial membrane permeability assay (PAMPA) has been adopted as the primary screening to assess the passive diffusion of compounds in the practical applications. A classical quantitative structure–activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(57 citation statements)
references
References 105 publications
(136 reference statements)
3
51
1
Order By: Relevance
“…Apart from prednisolone 21-sodium succinate (PSA = 141 Å), which has been classified as an outlier, PSA values for all steroids evaluated in the present study were below the cutoff value (PSA < 110 Å) suggested for the identification of poorly permeable compounds. Even though it's been recognized that lower PSA contributes to higher permeability [41], that trend was not confirmed here, mainly due to the absence of extreme variations in the PSA values and considering the relatively narrow range of PSA for the tested steroids.…”
Section: Interpretation Of Steroids Permeability Through Plscontrasting
confidence: 67%
See 2 more Smart Citations
“…Apart from prednisolone 21-sodium succinate (PSA = 141 Å), which has been classified as an outlier, PSA values for all steroids evaluated in the present study were below the cutoff value (PSA < 110 Å) suggested for the identification of poorly permeable compounds. Even though it's been recognized that lower PSA contributes to higher permeability [41], that trend was not confirmed here, mainly due to the absence of extreme variations in the PSA values and considering the relatively narrow range of PSA for the tested steroids.…”
Section: Interpretation Of Steroids Permeability Through Plscontrasting
confidence: 67%
“…The utility of in silico models in predicting drug permeability across biological membranes has been recognized as a time-and cost-efficient tool to facilitate drug discovery and development. The PLS model has been previously employed to identify the most critical molecular parameters affecting the permeability and retention of 17b-carboxamide steroids across an artificial membrane (parallel artificial membrane permeability assay (PAMPA)), as a means to predict their permeability across human skin [41]. In another study, Zhang et al, (2015) confirmed the good predictability of the PLS model, highlighting its potential utility as a high-throughput screening tool of placental drug permeability [18].…”
Section: Interpretation Of Steroids Permeability Through Plsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PAMPA was initially designed to estimate passive gastrointestinal absorption and blood-brain barrier permeability. A skin-PAMPA model was developed by adding synthetic certramides, cholesterol, and stearic acid [88]. In comparison to the diffusion cells, the PAMPA is preferred owing to its short time period required for the high-throughput screening of compounds for obtaining a permeation profile.…”
Section: Skin Parallel Artificial Membrane Permeability Assay (Skin-pmentioning
confidence: 99%
“…One is the human colon carcinoma (Caco-2) cell line permeability assay, and the other is the parallel artificial membrane permeability assay (PAMPA). In recent years, there have been numerous efforts to predict the absorption potential of compounds by using machine learning and molecular descriptors [119][120][121][122][123][124]. Fredlund et al [119] designed an in vitro assay to measure intrinsic permeability in Caco-2 cells and built prediction models with the data measured by a designed experiment.…”
Section: Absorptionmentioning
confidence: 99%